Antibiotic treatment for Burkholderia cepacia complex in people with cystic fibrosis experiencing a pulmonary exacerbation - Horsley, Alex (Cochrane Database Syst Rev, 2016)
BACKGROUND: Chronic pulmonary infection is a hallmark of lung disease in cystic fibrosis. Infections dominated by organisms of the Burkholderia cepacia complex, a group of at least 18 closely‐related species of gram‐negative bacteria, are particularly difficult to treat. These infections may be associated with a fulminant necrotising pneumonia. Burkholderia cepacia complex bacteria are resistant to many common antibiotics and able to acquire resistance against many more. Following patient segregation in cystic fibrosis medical care, the more virulent epidemic strains are not as frequent, and new infections are more likely to be with less virulent environmentally‐acquired strains. Although evidence‐based guidelines exist for treating respiratory exacerbations involving Pseudomonas aeruginosa, these cannot be extended to Burkholderia cepacia complex infections. This review, which is an update of a previous review, aims to assess the available trial evidence for the choice and application of treatments for these infections. OBJECTIVES: To assess the effectiveness and safety of different antibiotic regimens in people with cystic fibrosis experiencing an exacerbation and chronically infected with organisms of the Burkholderia cepacia complex. SEARCH METHODS: We searched the Cochrane Cystic Fibrosis Trials Register, compiled from electronic database searches and handsearching of journals and conference abstract books. We also searched the reference lists of relevant articles and reviews. Date of latest search: 28 August 2015. SELECTION CRITERIA: Randomised and quasi‐randomised controlled trials of treatments for exacerbations of pulmonary symptoms in people with cystic fibrosis chronically infected with organisms of the Burkholderia cepacia complex. DATA COLLECTION AND ANALYSIS: No relevant trials were identified. MAIN RESULTS: No trials were included in this review. AUTHORS' CONCLUSIONS: Burkholderia cepacia complex infections present a significant challenge for people with cystic fibrosis and their clinicians. The incidence is likely to increase as the cystic fibrosis population ages; and managing and treating these infections will become more important. There is a lack of trial evidence to guide decision making and no conclusions can be drawn from this review about the optimal antibiotic regimens for people with cystic fibrosis who have chronic Burkholderia cepacia complex infections. Clinicians must continue to assess each person individually, taking into account in vitro antibiotic susceptibility data, previous clinical responses and their own experience. Multicentre randomised clinical trials are needed to assess the effectiveness of different antibiotic regimens in people with cystic fibrosis infected with organisms of the Burkholderia cepacia complex.